Implementasi Metode Sam’iyah Syafawiyah pada Maharah Istima’ dan Maharah Kalam di PKPBA UIN Malang - Imamah, Anisul; Mahsunah, Mursyidatul; Syaputra, Prayoga; Aulia, Manisha; Fitriani, Laily (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
Methods have an important position in learning as a means to achieve a specific goal. The purpose of this research is to describe the use of the method of Sam'iyah Syafawiyah in an effort to improve the ability to hear and speak students in PKPBA UIN Malang. Maharah istima ' as maharah istiqbaliyah has an important role as a tool to collect information through hearing. The method of Sam'iyyah Syafawiyah proved to be a suitable approach to develop maharah istima', because it emphasizes the activity of listening as the beginning of learning, which is then implemented in the form of speaking. This research method uses a qualitative approach with a descriptive type of research, data collection techniques involve direct observation of student interaction during the application of the method, interviews with students and teachers, as well as the analysis of documents such as class notes and evaluation results. While the data analysis used in the form of data reduction, data display and conclusions. Data validation process is done by triangulating data based on collection techniques. The research was conducted at the Special Program for Arabic language development (PKPBA) UIN Maulana Malik Ibrahim Malang, Indonesia, in 2023 with the object of Student Research. The results showed that the steps of applying the method as follows, teachers can use YouTube as a learning tool, involving preliminary, repetitive, question and answer, and generalization. The results showed that students are able to respond well to audio and can pronounce words or sentences correctly. With the application of these methods in learning found some advantages and disadvantages when applied in PKPBA UIN Malang.